2003
DOI: 10.1055/s-2002-36428
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Pharmacokinetics and Pharmacodynamics of Insulin Lispro and Aspart in Healthy Volunteers

Abstract: Pharmacokinetic and pharmacodynamic profiles of the rapid-acting insulin analogues lispro and aspart were compared in a randomized, double-blind crossover study of 20 fasting healthy men following a single subcutaneous injection. Either insulin lispro or aspart, 0.05 U/kg-body-weight, was injected subcutaneously and followed by determination of 5-h profiles of plasma glucose, serum C-peptide and insulin concentrations. Lowest glucose concentrations were observed after 50 min in the aspart group (3.2 +/- 0.1 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 12 publications
0
13
0
2
Order By: Relevance
“…Unfortunately, acetaminophen was confirmed by blood testing in only 7 of the 17 patients and many patients presented after a period of time after ingestion when no considerable amount of acetaminophen (half life 1-4 hours) could be expected to be in the blood due to pharmacokinetic reasons (23,24). The authors were aware of the fact that the recruitment of the subjects under consideration was based solely on the information of physicians contacting the poison center network.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, acetaminophen was confirmed by blood testing in only 7 of the 17 patients and many patients presented after a period of time after ingestion when no considerable amount of acetaminophen (half life 1-4 hours) could be expected to be in the blood due to pharmacokinetic reasons (23,24). The authors were aware of the fact that the recruitment of the subjects under consideration was based solely on the information of physicians contacting the poison center network.…”
Section: Discussionmentioning
confidence: 99%
“…In studies that have directly compared the absorption rate and glucose control of one rapid‐acting insulin analogue with another, few PK/PD differences have been noted. Of five studies that compared insulin lispro and insulin aspart, only two detected a significant difference [13–17]. In one of them, a randomized, crossover trial in 14 people with type 1 diabetes, subcutaneous injection of insulin lispro reached maximum insulin concentration significantly earlier than insulin aspart (p = 0.02) and declined to 50% of the peak insulin concentration significantly earlier (p = 0.02) [13].…”
Section: Methodsmentioning
confidence: 99%
“…References from retrieved publications provided additional material and were used to expand the period of time from which data were assembled. A total of 19 papers were identified with results of PK/PD studies for rapid-acting analogues: 11 for insulin lispro [10][11][12][13][14][15][16][17][18][19][20], 10 for insulin aspart [13][14][15][16][17][21][22][23][24][25] and 9 for insulin glulisine [11,[18][19][20]23,24,[26][27][28]. Some studies included more than one analogue.…”
Section: Methodsmentioning
confidence: 99%
“…An randomized double-blind study in healthy males comparing insulin lispro and aspart6 showed a 10-minute difference in the time to maximal reduction, favoring insulin aspart, but no difference in the glucose control response. Two studies done in patients with type 1 diabetes mellitus5,7 showed very similar peak times for both insulin aspart and lispro (approximately 40 minutes in both studies) and time to reach 50% of the peak (approximately 20 minutes).…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%